Adult bacterial conjunctivitis: resistance patterns over 12 years in patients attending a large primary eye care centre in the UK. Issue 1 (11th November 2016) - Silvester, Alexander; Neal, Timothy; Czanner, Gabriela; Briggs, Michael; Harding, Simon; Kaye, Stephen
Abstract : Purpose: To determine whether there was a change in the resistance pattern of bacteria isolated from cases of conjunctivitis following the introduction of over-the-counter availability of chloramphenicol in 2005. Design and setting: Retrospective review of laboratory records for adult patients with suspected bacterial conjunctivitis between 2001 and 2012 attending the Royal Liverpool University Hospital. Participants: Patients with suspected bacterial conjunctivitis. Organisms were identified by standard laboratory methods. Scanty growth and normal flora were considered as a negative result. For positive results, susceptibility testing was undertaken as per British Society for Antimicrobial Chemotherapy guidelines. Main outcome measures: Prevalence of groups of bacteria associated with acute conjunctivitis and their resistance to chloramphenicol, ciprofloxacin, gentamicin, and methicillin. Results: A total of 8209 conjunctival swabs were reviewed; 1300 (15.8%) were considered positive, of which 977 (75.2%) and 323 (24.8%) bacteria were identified as Gram positive and Gram negative, respectively. Staphylococcus aureus was the most prevalent organism identified. Resistance of all bacterial isolates to chloramphenicol was 8.4% varying from 3.0% to 16.4% while that for ciprofloxacin and gentamicin was 16.4% and 14.0%, respectively. Methicillin resistance among S. aureus was 8.3%. Conclusion: Resistance to chloramphenicol has remained stable since being made available over the counter. Among Gram-positive bacteria, the most prevalent causative agent of bacterial conjunctivitis, chloramphenicol sensitivity remains high.